High‐fat diet pre‐conditioning improves microvascular remodelling during regeneration of ischaemic mouse skeletal muscle. (23rd February 2020) - Nwadozi, Emmanuel; Rudnicki, Martina; De Ciantis, Matthew; Milkovich, Stephanie; Pulbere, Alexandru; Roudier, Emilie; Birot, Olivier; Gustafsson, Thomas; Ellis, Christopher G.; Haas, Tara L.
Abstract: Aim: Critical limb ischaemia (CLI) is characterized by inadequate angiogenesis, arteriolar remodelling and chronic myopathy, which are most severe in type 2 diabetic patients. Hypertriglyceridaemia, commonly observed in these patients, compromises macrovascular function. However, the effects of high‐fat diet‐induced increases in circulating lipids on microvascular remodelling are not established. Here, we investigated if high‐fat diet would mimic the detrimental effect of type 2 diabetes on post‐ischaemia vascular remodelling and muscle regeneration, using a mouse model of hindlimb ischaemia. Methods: Male C57Bl6/J mice were fed with normal or high‐fat diets for 8 weeks prior to unilateral femoral artery ligation. Laser doppler imaging was used to assess limb perfusion recovery. Vascular recovery, inflammation, myofibre regeneration and fibrosis were assessed at 4 or 14 days post‐ligation by histology and RNA analyses. Capillary‐level haemodynamics were assessed by intravital microscopy of control and regenerating muscles 14 days post‐ligation. Results: High‐fat diet increased muscle succinate dehydrogenase activity and capillary‐level oxygen supply. At 4 days post‐ligation, no diet differences were detected in muscle damage, inflammatory infiltration or capillary activation. At 14 days post‐ligation, high fat‐fed mice displayed accelerated limb blood flow recovery, elevated capillary and arteriole densities as well as greater red blood cell supply rates and capillary‐level oxygen supply. Regenerating muscles from high fat‐fed mice displayed lower interstitial fat and collagen deposition. Conclusion: The muscle‐level adaptations to high‐fat diet improved multiple aspects of muscle recovery in response to ischaemia and did not recapitulate the worse outcomes seen in diabetic CLI patients.